Diversity and Pathogenicity of Fusarium temperatum Scaufl. & Munaut causing Fusarium ear rot of maize (Zea mays L.) in major maize growing agroecosystems of Ethiopia - Deressa, Temesgen; Girma Adugna; Mahabaleswara, Suresh L.; Zelalem Bekeko; Vaughan, Martha; Opoku, Joseph (Springer, 2025)
Maize (Zea mays L.) is widely grown in Ethiopia under diverse agro-climatic conditions and it is a critical food security crop in the country. However, maize Fusarium ear rot (FER) disease caused by Fusarium species; primarily by F. proliferatum (Matsushima) Nirenberg, F. subglutinans (Wollenweber & Reinking) Nelson, and F. verticillioides (Saccardo) Nirenberg is one of the main sources of yield reduction and mycotoxin contamination. During 2020–2021, the FER of maize was assessed on the farmer’s field in western major maize growing belts of Western Ethiopia. Morphological and microscopic observations were made to identify the pathogen associated to the ear rot of maize. Molecular characterization of the pathogen was also made. A portion of the translation elongation factor 1-α (TEF1-α) was amplified using primers EF1 (ATGGGTAAGGARGACAAGAC) and EF2 (GGARGTACCAGTSATCATG) and bidirectionally sequenced using primers EF3 (GTAAGGAGGASAAGACTCACC) and EF22i (AGGAACCCTTACCGAGCTC), and two non-contiguous fragments of the RNA polymerase II subunit (RPB2). BLAST queries were also performed in Fusarium-ID. The comparison of the sequence with established reference sequences; NRRL 13,291 and CBS 138,287 revealed 100% sequence identity with F. temperatum isolates. A phylogenetic tree was constructed with concatenated sequences of the two genes. Pathogenicity test was conducted by inoculating healthy maize ears with F. temperatum macro-conidia suspension. Koch’s postulates were fulfilled by the pathogen (F. temperatum) re-isolation and identification. Hence, the morphological and molecular characterization of the pathogen revealed that the identified pathogen was F. temperatum.